Lethal COG6‐CDG in neonatal patient with arachnodactyly, joint contractures, and skin manifestations: Founder mutation in the Southeastern European population?. Issue 2 (19th January 2022) - Ververi, Athina; Stathopoulou, Theodora; Kontou, Aggeliki; Farini, Maria; Vlahou, Georgia; Demiris, Nikolaos; Sarafidis, Kosmas
Abstract: Herein, we report a lethal case of the ultra‐rare COG6‐congenital disorder of glycosylation (CDG) presenting with skin manifestations (scaling and erosions) and joint contractures in a neonate of Albanian origin. The patient was homozygous for a COG6 pathogenic variant, previously reported in another three individuals of Greek, Bulgarian and Turkish descent. The presence of a founder mutation in the geographical area is possible. The index case emphasizes the need to consider CDGs in neonatal patients with skin manifestations and joint contractures, particularly patients of Southeastern European or West Asian origin.